Influence of Auxins on Rooting of Stem Cuttings of the Small- Leaved White Crossby (Gudaim), Grewia tenax (Forsk) - El-Siddig, Kamal; B. S. Gama, Peter; Inanaga, Shinobu (Gezira Journal of Agricultural Science; Vol 3 No 1 (2005), 2021)
The small-leaved white crossberry (Gudaim), Grewia tenax (Forsk( Fiori , is a deciduous, tropical shrub or tree valued for its fruit. Being high in iron content, the fruit is considered as a simple safeguard against iron-deficiency anemia. In spite of this, the fruit is exploited from the wild and there have been little or no efforts to domesticate and cultivate this species. Information on the vegetative propagation of this species is not available at the present time. A series of nursery experiments were conducted during March-June 2003 to assess the effects of auxin source ]indole acetic acid (IAA), indole-3-butyric acid (IBA) and -phthalene acetic acid (NAA)], concentration (0, 1000, 1500 and 2000 ppm( duration of exposure (quick dip, one-minute dip and five-minutes dip )and form (liquid versus powder) on adventitious root formation in stem cuttings. Significant stimulation of rooting was observed with IBA at all concentrations and with IAA at 1000 and 1500 ppm. NAA, at all concentrations, was ineffective in promoting root formation. Maximum rooting success with IBA was achieved at 1500 ppm (43%) and with IAA at 1000 ppm (37%). Short-term exposure (quick dip or one-minute dip( of the cut surface to 1500 ppm IBA solution resulted in greater rooting success (57%-61%) than a five-minutes dip (32%). IBA talcum powder worked slightly better than in liquid form (56% versus 52%). It was concluded that application of 1500 ppm IBA as a quick dip in liquid or powder form is the most suitable treatment for rooting of stem cuttings of this species.